Experiences and coping with the altered body image in digestive stoma patients - César Hueso-Montoro; Candela Bonill-; Miriam Celdrán-Mañas; Sandra Milena Hernández-Zambrano; Manuel Amezcua-Martínez; José Miguel Morales-Asencio
ABSTRACT Objective: to describe the coping of stoma patients with the news about the ostomy, as well as to analyze the meaning and the experience of their new bodily reality. Method: qualitative phenomenological study undertaken through semistructured interviews with 21 stoma patients. The analysis was based on the constant comparison of the data, the progressive incorporation of subjects and triangulation among researchers and stomal therapy nurses. The software Atlas.ti was used. Results: two main categories emerge: "Coping with the news about receiving a stoma" and "Meaning and experience of the new bodily reality". The informants' answer varies, showing situations that range from the natural acceptance of the process to resignation and rejection. The previous experiences of other family members, the possible reconstruction of the stoma or the type of illness act as conditioning factors. Conclusions: the coping with the news about the stoma is conditioned by the type of illness, although the normalization of the process is the trend observed in most informants. Nursing plays a fundamental role in the implementation of cognitive-behavioral interventions and other resources to promote the patients' autonomy in everything related to care for the stoma.